GOVERNANCE OF MINERAL AND COAL MINING PERMITS: LEGAL DYNAMICS IN INDONESIA AND NIGERIA - Hezron Sabar Rotua Tinambunan; Istislam Istislam; Shinta Hadiyantina; Adi Kusumaningrum; Ngboawaji Daniel Nte (Diponegoro Law Review, 2025)
This study examines the legal construction of authority for mineral and coal mining permits in Indonesia and Nigeria, using a normative approach grounded in statutory analysis and critical legal reasoning. It examines how central regional power configurations shape the effectiveness and justice of mining-licensing governance. The study finds that Indonesia’s regulatory framework, particularly since the enactment of the Mineral and Coal Mining Law and the Job Creation Law, consolidates licensing authority at the central level, reducing regional participation and limiting protections for indigenous and local communities. Similarly, Nigeria’s centralized licensing regime generates distributional inequities, weak transparency, and persistent conflict in resource-rich regions. The comparative findings demonstrate that excessive centralization, without substantive spatial and community participation, creates governance gaps and risks legitimacy. The study concludes that mining licensing systems in both jurisdictions require reconstruction toward a participatory decentralization model that incorporates regional involvement, community rights, and ecological justice. These insights offer implications for the design of more equitable, transparent, and sustainable natural resource governance.